A flexible control system designed for lab-scale simulations and optimization of composting processes. (February 2018) - Oazana, Sh.; Naor, M.; Grinshpun, J.; Halachmi, I.; Raviv, M.; Saadi, I.; Avidov, R.; Varma, V. Sudharsan; Rosenfeld, L.; Gross, A.; Laor, Y.
Graphical abstract: Highlights: A new composting simulator was built with high control flexibility. Three heating modes and three aeration modes are programmed. High control flexibility is achieved by 9 possible heating/aeration combinations. A series of demonstrations shows program validity and potential uses. Abstract: Understanding and optimization of composting processes can benefit from the use of controlled simulators of various scales. The Agricultural Research Organization Composting Simulator (ARO-CS) was recently built and it is flexibly automated by means of a programmable logic controller (PLC). Temperature, carbon dioxide, oxygen and airflow are monitored and controlled in seven 9-l reactors that are mounted into separate 80-l water baths. The PLC program includes three basic heating modes (pre-determined temperature profile, temperature-feedback ("self-heating"), and carbon dioxide-dependent temperature), three basic aeration modes (airflow dependence on temperature, carbon dioxide, or oxygen) and enables all possible combinations among them. This unique high flexibility provides a robust and valuable research tool to explore a wide range of research questions related to the science and engineering of composting. In this article the logic and flexibility of the control system is presented and demonstrated and its potential applications are discussed.